Predicting substance use disorder using long-term attention deficit hyperactivity disorder medication records in Truven. (June 2020) - Fouladvand, Sajjad; Hankosky, Emily R; Bush, Heather; Chen, Jin; Dwoskin, Linda P; Freeman, Patricia R; Henderson, Darren W; Kantak, Kathleen; Talbert, Jeffery; Tao, Shiqiang; Zhang, Guo-Qiang
About 20% of individuals with attention deficit hyperactivity disorder are first diagnosed during adolescence. While preclinical experiments suggest that adolescent-onset exposure to attention deficit hyperactivity disorder medication is an important factor in the development of substance use disorder phenotypes in adulthood, the long-term impact of attention deficit hyperactivity disorder medication initiated during adolescence has been largely unexplored in humans. Our analysis of 11, 624 adolescent enrollees with attention deficit hyperactivity disorder in the Truven database indicates that temporal medication features, rather than stationary features, are the most important factors on the health consequences related to substance use disorder and attention deficit hyperactivity disorder medication initiation during adolescence.